Investigating two different training time frame during Ramadan fasting - Kordi, R.; Abdollahi, M.; Memari, A. -H.; Najafabadi, M. G. (Asian Journal of Sports Medicine, 2011)
Purpose: Muslim athletes may continue training and competing while they are fasting. There is a concern about negative effects of fasting on sports performance. This study aimed to investigate the influence of two training time frames on athletes` body composition and performance during Ramadan fasting. Methods: An observational study was conducted and thirty four male volunteer athletes from different sports including volleyball, karate, taekwondo and football were assigned in two groups. The first group included 14 elite athletes who during Ramadan voluntarily participated in training sessions at 1 hour before Iftar (BI) and the second group of 20 elite athletes who during Ramadan participated in training sessions at 3 hours after Iftar (AI). Testing was performed one week before; in the first and fourth weeks of Ramadan and one week after Ramadan. Weights, heights and skinfold thickness were assessed at each time point and body mass index was calculated. Each player was assessed for agility and explosive strength as well. Results: The mean weight and body mass index of both groups decreased significantly during Ramadan (P<0.001). Performance variables were not negatively affected by fasting in BI or AI group athletes. Conclusions: Weight reduction might come with either BI or AI training schedules in Ramadan. Daytime or evening training did not inversely affect the agility and power performances in a group of elite athletes during Ramadan fasting.